Israeli teachers' attitudes toward parental involvement in school: A qualitative study - Dor, Asnat (International Journal about Parents in Education, 2023)
The aim of this qualitative study is to gain in-depth understanding of teachers' views and attitudes toward parental involvement in school. Twenty seven Israeli elementary-school and secondary-school teachers were interviewed and asked to define parental involvement, their feelings toward it, and its challenges and benefits. Our findings revealed relatively high level of inconsistency between declared positive attitudes and perceived challenges and threat. This inconsistency manifests a need for significant progress in teacher-parent relationship in Israel. The practical implications of this study are that training programs should be constructed to improve teacher-parent collaboration, focusing on ways of reducing teachers’ tension and enhancing their understanding of the possibilities and potential outcomes of parents’ involvement.